IMPLEMENTASI TEKNOLOGI NFC UNTUK RECORDING DATA SAPI PERAH KELOMPOK TANI LEMBU ALAM SERAMBI KOTA PADANG PANJANG - Ratna Aisuwarya; Mohammad Hafiz Hersyah; Rahmi Eka Putri; Rian Ferdian; Fatimah Fatimah (Journal of Appropriate Technology for Community Services, 2020)
One of the efforts in increasing the productivity of dairy cows is to apply maintenance management to dairy cows in the form of recording livestock data. Lembu Alam Serambi farmer group has a recording system using livestock cards provided by the Animal Husbandry Department. Cattle cards used for data recording of dairy cows are made from a type of paper that has several disadvantages, namely, easily lost, torn, wet, burned, and dirty. Therefore, to overcome this problem, we apply Android using Near Field Communication (NFC) technology. In this community service, the NFC technology implementation system is integrated with cow's ear tag and android application. This system is used to identify dairy cows and process data recording with an Android-based application. In this cow data recording system consists of two mobile apps, namely cow data record application and NFC tap tag application. The system implementation shows that the community service activity can help facilitate the Lembu Alam Serambi farmer group in the process of recording dairy cattle data.